Reproducibility and replicability in research: What 452 professors think in Universities across the USA and India - Chakravorti, Tatiana; Koneru, Sai; Rajtmajer, Sarah (PLOS ONE, 2025)
In the past decade, open science and science of science communities have initiated innovative efforts to address concerns about the reproducibility and replicability of published scientific research. In some respects, these efforts have been successful, yet there are still many pockets of researchers with little to no familiarity with these concerns, subsequent responses, or best practices for engaging in reproducible, replicable, and reliable scholarship. In this study, we surveyed 452 professors from universities across the USA and India to understand perspectives on scientific processes and identify key points for intervention. Our findings reveal both national and disciplinary gaps in attention to reproducibility and transparency in science, aggravated by incentive misalignment and resource constraints. We suggest that solutions addressing scientific integrity should be culturally-centered, where definitions of culture should include both regional and domain-specific elements. This study examines research cultures in India and the USA across a diverse range of social science and engineering disciplines. The universities included in the study were carefully selected to represent various regions of each country and reflect institutions across different ranking levels, ensuring a broad and representative sample. While the findings provide valuable insights into the research environments of India and the USA, their applicability is limited to these two countries and respective disciplines. The survey relies on self-reported data, which can be subject to biases, e.g., social desirability or recall bias. Future research will expand the scope to include additional countries, allowing for a more comprehensive comparison of global research cultures. Additionally, we aim to investigate how regional, institutional, and disciplinary factors influence research practices and collaboration across borders, providing a deeper understanding of international academic environments.